2013
DOI: 10.1002/eat.22113
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the glucocorticoid receptor gene promoter in bulimic women: Associations with borderline personality disorder, suicidality, and exposure to childhood abuse

Abstract: Objective: To compare levels of methylation of the glucocorticoid receptor (GR) gene (NR3C1) promoter between women with bulimia nervosa (BN) and women with no eating disorder (ED), and also to explore, in women with BN, the extent to which methylation of the GR gene promoter corresponds to childhood abuse, suicidality, or borderline personality disorder (BPD). Method:We measured methylation levels in selected NR3C1 promoter regions using DNA obtained from lymphocytes in 64 women with BN (32 selected as having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 36 publications
3
93
3
4
Order By: Relevance
“…Additionally, Yehuda et al (2014) reported mean hypomethylation of 1 F promoter in PTSD subjects. In contrast to the findings reviewed above, Steiger et al (2013) found no associations between 1 F methylation and either BPD, history of suicidality or childhood abuse.…”
Section: Study Methodology Findingscontrasting
confidence: 80%
See 3 more Smart Citations
“…Additionally, Yehuda et al (2014) reported mean hypomethylation of 1 F promoter in PTSD subjects. In contrast to the findings reviewed above, Steiger et al (2013) found no associations between 1 F methylation and either BPD, history of suicidality or childhood abuse.…”
Section: Study Methodology Findingscontrasting
confidence: 80%
“…Additionally, a second research group (De Rooij et al, 2012) analyzed a region specifically spanning exon 1 C (excluding its promoter region from the analysis). Steiger et al (2013) found no epigenetic correlates of experiencing childhood abuse in BN subjects with or without BPD. Nevertheless, they did observe a set of differential CpG-specific hypermethylation patterns in both BN-BPD subjects when compared to controls without eating disorders, and in BN individuals with a history of suicidality when compared to controls.…”
Section: Nr3c1 Gene -1 C Regionmentioning
confidence: 87%
See 2 more Smart Citations
“…One study for example reported a significant positive correlation between methylation status of the promoter region of the glucocorticoid receptor gene clinical severity (MartinBlanco et al, 2014). Another study showed that in a sample of bulimic patients comorbid BPD was associated with significantly more methylation (Steiger et al, 2013). Future research is warranted here.…”
Section: Altered Gr/mr Functionmentioning
confidence: 92%